2012
DOI: 10.1016/j.pbb.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

mGluR5 receptors in the basolateral amygdala and nucleus accumbens regulate cue-induced reinstatement of ethanol-seeking behavior

Abstract: Pharmacological blockade of the type 5 metabotropic glutamate receptor (mGluR5) attenuates cue-induced reinstatement of ethanol-seeking behavior, yet the brain regions involved in these effects are not yet known. The purpose of the present study was to determine if local blockade of mGluR5 receptors in the basolateral amygdala (BLA) and/or the nucleus accumbens (NAc), two brain regions known to be involved in stimulus-reward associations, attenuates the reinstatement of ethanol-seeking behavior induced by etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 62 publications
3
81
0
Order By: Relevance
“…Indeed, our laboratory has detected alcohol-induced changes in Acb levels of mGlu5 in some (Figure 5B; Goulding et al, 2011; Cozzoli et al, 2012), but not all studies (Szumlinski et al, 2007), which may reflect differences in the subregions examined, route of administration/drinking paradigm employed. Nevertheless, intact mGlu5 function within Acb subregions, notably the AcbSh, is important for binge-drinking behavior (Cozzoli et al, 2009; Besheer et al, 2010; Sinclair et al, 2012). Therefore, behavioral differences could be driven by changes in receptor function that are not reflected in changes in total protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our laboratory has detected alcohol-induced changes in Acb levels of mGlu5 in some (Figure 5B; Goulding et al, 2011; Cozzoli et al, 2012), but not all studies (Szumlinski et al, 2007), which may reflect differences in the subregions examined, route of administration/drinking paradigm employed. Nevertheless, intact mGlu5 function within Acb subregions, notably the AcbSh, is important for binge-drinking behavior (Cozzoli et al, 2009; Besheer et al, 2010; Sinclair et al, 2012). Therefore, behavioral differences could be driven by changes in receptor function that are not reflected in changes in total protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Drug reinforcement is attributed to various brain reward regions, in particular the PFC (Goldstein and Volkow, 2002), NAc (Childress et al, 1999, Obara et al, 2009), and AMG (Zarrindast et al, 2010, Sinclair et al, 2012, Christian et al, 2013). While it is well known that dopamine is one of the major neurotransmitters responsible for the development of drug dependence (Anderson and Swanson, 2000, Ito et al, 2004), studies focusing on these brain reward centers have clearly demonstrated an underlying relationship between glutamatergic transmission and ethanol abuse (Carrara-Nascimento et al, 2011, Gass et al, 2011, Mishra et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…mGlu5 signaling on striatal Dopamine-D1 receptor expressing neurons is necessary for both novelty-seeking behavior and the abstinence-induced escalation of alcohol drinking in mice (Parkitna et al, 2013). mGlu5 receptors in the basolateral amygdala and nucleus accumbens regulate cue-induced reinstatement of ethanol-seeking behavior (Sinclair et al, 2012). Thus, although SNPs in GRM5 did not meet the stringent genome-wide significant threshold in the study by Bierut et al, 2010, results from human alcoholic brain and animal models of alcohol dependence support a key role of GRM5 in alcohol dependence phenotypes and the negative affective state during protracted abstinence.…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%